Group 2 ITI Consensus Report: Prosthodontics and implant dentistry - Morton, Dean; Gallucci, German; Lin, Wei-Shao; Pjetursson, Bjarni; Polido, Waldemar; Roehling, Stefan; Sailer, Irena; Aghaloo, Tara; Albera, Hugo; Bohner, Lauren; Braut, Vedrana; Buser, Daniel; et al. (Clinical Oral Implants Research, 2018)
OBJECTIVES: Working Group 2 was convened to address topics relevant to prosthodontics and dental implants. Systematic reviews were developed according to focused questions addressing (a) the number of implants required to support fixed full-arch restorations, (b) the influence of intentionally tilted implants compared to axial positioned implants when supporting fixed dental prostheses (FDPs), (c) implant placement and loading protocols, (d) zirconia dental implants, (e) zirconia and metal ceramic implant supported single crowns and (f) zirconia and metal ceramic implant supported FDPs. MATERIALS AND METHODS: Group 2 considered and discussed information gathered in six systematic reviews. Group participants discussed statements developed by the authors and developed consensus. The group developed and found consensus for clinical recommendations based on both the statements and the experience of the group. The consensus statements and clinical recommendations were presented to the plenary (gathering of all conference attendees) and discussed. Final versions were developed after consensus was reached. RESULTS: A total of 27 consensus statements were developed from the systematic reviews. Additionally, the group developed 24 clinical recommendations based on the combined expertise of the participants and the developed consensus statements. CONCLUSIONS: The literature supports the use of various implant numbers to support full-arch fixed prostheses. The use of intentionally tilted dental implants is indicated when appropriate conditions exist. Implant placement and loading protocols should be considered together when planning and treating patients. One-piece zirconia dental implants can be recommended when appropriate clinical conditions exist although two-piece zirconia implants should be used with caution as a result of insufficient data. Clinical performance of zirconia and metal ceramic single implant supported crowns is similar and each demonstrates significant, though different, complications. Zirconia ceramic FDPs are less reliable than metal ceramic. Implant supported monolithic zirconia prostheses may be a future option with more supporting evidence.
EVALuna2:214274